Con Pasión Absoluta: reconstrucción histórica de la Guatemala de los ochentas a través de la mirada femenina. - Calderón-Rojas, Ericka (2015)
Carol Liliana Zardetto de la Vega is the author of this work bestowed with the Central American Novel Award, 2004.   The political history of Guatemala is one of frames developed in the novel recreated, according to my judgment, from a feminine perspective which raises a reencounter of the collective and individual memory of the protagonist.